2019
DOI: 10.1186/s12888-019-2358-2
|View full text |Cite
|
Sign up to set email alerts
|

Differential executive functioning in the topology of Spirit possession or dissociative disorders: an explorative cultural study

Abstract: BackgroundIn Oman, anecdotal and impressionistic observation have helped parse and categorize various manifestations of spirit possession into two broad and distinct categories: intermittent dissociative phenomenon and transitory dissociative phenomenon. The primary aim of the present study was to compare the performance of participants on neuropsychological tests among different grades of possession. Other correlates were also sought.MethodsAssessment criteria for the two groups included measures examining ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…This study has strong points: Provides insight that may help understand cognitive skills in practitioners of mediumistic trance. Contradicts previous findings from Al-Adawi et al (2019) because an executive dysfunction was highly prevalent in practitioners of possession, and seeks to support future studies to define the risk of cognitive impairment in practitioners of mediumistic trance.…”
Section: Strengths and Limitationsmentioning
confidence: 89%
See 3 more Smart Citations
“…This study has strong points: Provides insight that may help understand cognitive skills in practitioners of mediumistic trance. Contradicts previous findings from Al-Adawi et al (2019) because an executive dysfunction was highly prevalent in practitioners of possession, and seeks to support future studies to define the risk of cognitive impairment in practitioners of mediumistic trance.…”
Section: Strengths and Limitationsmentioning
confidence: 89%
“…Another study suggested that performance on the verbal fluency test was significantly different among participants with intermittent dissociative phenomena when compared to transient dissociative phenomena ( Al-Adawi et al, 2019 ). Such a finding did not corroborate the current study’s outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We assessed different cognitive domains of attention and concentration (Digit Span) [23], learning and remembering (California Verbal Learning Test) [24], executive function (Wisconsin Card Sorting Test [25], processing speed (Digit Symbol) [26] and speech and language [27]. For brevity, performance on each test has been expressed in percentile scores as detailed elsewhere [28] based on normative data from Omani populations [25,27].…”
Section: Neuropsychological Functioningmentioning
confidence: 99%